LEARNING ACHIEVEMENT BETWEEN STUDENTS TEACHED USING THE DIRECT TEACHING MODEL ASSISTED WITH PAPER CARDBOARD MEDIA AND ICT MEDIA ON FLAT SIDE SPACE CONSTRUCTION MATERIALS - Agus Subaidi; Septi Dariyatul Aini; Lili Supardi; Amaliya Rahmahwati; Aan Hidayat (Jurnal Scientia, 2022)
This study aims to determine whether or not there is a difference in learning achievement between students who are taught using a direct teaching model assisted by cardboard media and ICT media on flat sided geometric material. While the research method used is quantitative and comparative research because the data obtained is in the form of numbers from the test results and from the test results the difference can be seen. The population in the study were all fifth grade students at SD Plus Nurul Hikmah Pamekasan. Researchers used a purposive random sampling technique in determining the research sample. Class VA as the control class as many as 21 students and class VD as the experimental class as many as 23 students. The data collection technique used is a test in the form of essay questions. While the data analysis technique used is the t-test. Based on the results of data analysis, the value of tcount = 1.92 and ttable = 2.021 with dk = (23+21-2) = 42 at a significant level of 5%. Thus tcount < ttable means that H0 is accepted and H1 is rejected. So it can be concluded that there is no difference in learning achievement between students who are taught using a direct teaching model assisted by cardboard media and ICT media on flat sided geometric material.